Magnetic phase diagram and magnetoelastic coupling of NdB4 studied by high-resolution capacitance dilatometry up to 35 T - Ohlendorf, Rahel; Spachmann, Sven; Fischer, Lukas; Carstens, Frederik Leon; Brunt, D.; Balakrishnan, G.; Petrenko, Oleg A.; Klingeler, Rüdiger (Physical review, 2023)
We report high-resolution dilatometry studies on single crystals of the Shastry-Sutherland-lattice magnet NdB4 supported by specific heat and magnetometry data. Our dilatometric studies evidence pronounced anomalies at the phase boundaries, which imply strong magnetoelastic coupling. The evolution of the three zero-field phase transitions separating distinct antiferromagnetic phases at 𝑇N=17.2 K, 𝑇IT=6.8 K, and 𝑇LT=4.8 K can thus be traced in applied magnetic fields, which provides the magnetic phase diagrams for 𝐵∥𝑐 up to 15 T and for 𝐵∥[110] up to 35 T. In-field phases are discovered for both field directions and already known phases are confirmed. In particular, phase boundaries between different phases are unambiguously shown by sign changes of observed anomalies and corresponding changes in uniaxial pressure effects. For 𝐵⁢||⁢𝑐, we find a 1/4-magnetization plateau in addition to a previously reported plateau at 1/5 of the saturation magnetization. 𝑇N increases for 𝐵∥𝑐 in fields up to 15 T implying that magnetic moments of the all-in/all-out structure in the high-temperature AFM ordered phase are driven towards the 𝑐 axis in high magnetic fields. Uniaxial pressure dependencies 𝜕𝑇crit/𝜕𝑝c of the phase transition temperatures for magnetic fields and pressure applied along the 𝑐 axis are derived from the data.
Gesehen am 23.09.2024
Die Ziffer "4" ist im Titel bei NDB4 tiefgestellt